Interactive group nutritional education: achieving lasting lifestyles changes - deBeausset Stanton, Indira (2017)
Interactive Group Nutritional Education is a process by which the participants not only transform their own thinking and habits but also take actions to change their environment; it promotes the adoption of healthy lifestyles and adherence to treatments for chronic diseases, which significantly improves quality of life. The author explains the epistemological foundation of constructs and the educational method she developed using elements of the constructivist learning theory and critical pedagogy. This method has been evolving and refined for more than 20 years at the School of Nutrition of the Faculty of Medicine of the University of Costa Rica, and it has been proven effective in achieving better adherence to treatment because it produces changes in attitudes due to the internalization by participants of their own resources and motivations for change. This paper was produced as part of Project Pry01-1366-2016 of the University of Costa Rica.